Straticyte demonstrates prognostic value over oral epithelial dysplasia grade for oral potentially malignant lesion assessment. (September 2017) - Hwang, Jason T.K.; Gu, Ying R.; Dickson, Benjamin J.; Shen, Mi; Ralhan, Ranju; Walfish, Paul G.; Mock, David; Pritzker, Kenneth P.H.
Highlights: Straticyte is more clinically useful than OED grading for cancer risk prediction. Straticyte is quantitative and objective with few inter-observer variations. Straticyte grade supplements histopathological dysplasia assessment. Abstract: Objectives: Straticyte™ was previously shown to be a more effective prognostic assessment than the current standard of care, histopathological dysplasia grading, to assess progression risk of oral epithelial dysplasia to invasive cancer [Hwang JT, Gu YR, Shen M, Ralhan R, Walfish PG, Pritzker KP, et al. Individualized five-year risk assessment for oral premalignant lesion progression to cancer. Oral Surg Oral Med Oral Pathol Oral Radiol. 2017;123:374–81]. In this follow-up study, our aim is to confirm the prognostic value of Straticyte using an independent cohort of oral biopsy cases previously assessed as epithelial dysplasia of various grades. Materials and methods: Using Visiopharm image analysis system, we analyzed an independent retrospective cohort of 51 oral biopsy samples with known outcomes and a follow-up history of up to 12 years, to verify Straticyte, an individualized 5-year risk assessment for progression of oral potentially malignant lesions to invasive squamous cell carcinoma. Results: Straticyte classified the lesions more accurately than histopathological oral epithelial dysplasia grading for risk for progression to cancer over five years. The sensitivity of low-risk vs. non-low-risk Straticyte groups was 100% compared to 68% for mild vs. non-mild dysplasia. The sensitivity of high-risk vs. non-high-risk Straticyte was 71% compared to 3% for severe vs. non-severe dysplasia. Furthermore, the Negative Predictive Value (NPV) for Straticyte was 100% for low-risk vs. non-low-risk, whereas the NPV for mild vs. non-mild dysplasia was 38%. Conclusion: In this cohort, Straticyte ascertains as a more useful assessment for risk of cancer progression in oral potentially malignant lesions than oral epithelial dysplasia grade.